ANALISIS MODEL BISNIS PADA PT SOKA CIPTA NIAGA BANDUNG KEDALAM PENDEKATAN BISNIS MODEL CANVAS MENGGUNAKAN PETA EMPATI - RESI RESMAWATI (Akademi Sekretari Manajemen Taruna Bakti, 2021)
A company in running its business process requires the design of a Business Model with the aim that the business process will be by following the expectations desired by the company. The purpose of the research was to make the design of the business model by using an Empathy Map of the socks that received the first Halal certification from the Majelis Ulama Indonesia, for the socks industry. The method of research conducted is using The Qualitative Method, done by collecting data in interviews with consumers of Soka socks with Triangulation Technique. There were four informants selected, namely with different ages, occupations and interview location. All selected informants were women and had used Soka Socks for more or less three years. The results obtained in the interview process to the consumers of Soka socks will be analyzed to become the design of The Empathy Map and Business Model Canvas for PT Soka Cipta Niaga.